Correlation of initial serum lactic acid and base deficit with early mortality in patients with major thermal burns at a Kenyan Tertiary Hospital - Muriithi Eliud Kennedy; Nangole Ferdinand Wanjala; Mwangi Peter Wambugu; Ayieko Philip (Elsevier, 2023)
Objective: To correlate initial serum lactic acid and base deficit (BD) levels with early mortality in major thermal burns. Methods: This was a prospective descriptive study conducted over 6 months at Kenyatta National Hospital (KNH), Nairobi, Kenya. Ninety consecutive patients with major thermal burns exceeding 20% of total body surface area (TBSA), who met other inclusion criteria participated. Biographic and clinical data were collected using a structured questionnaire. Blood samples were drawn at admission for arterial blood gas analysis (ABGAs) to obtain serum lactic acid and BD levels. Patients were followed up for 7 days at KNH Burns Unit. Results: Studied patients had burns from 21% to 100% TBSA. Majority, 54(60%), had burns between 21% and 50% TBSA. 55(61.1%) patients died within 7 days after admission. 38(69.1%) of these deaths occured within the initial 48 h. Both mean serum lactic acid (P < 0.001) and BD (P < 0.001) levels were statistically associated with mortality in 7 days, compared with the 7-day survivors. On average, patients who died had higher serum lactic acid (2.8 mmol/L versus 5.1 mmol/L) and lower BD (-9.8 mmol/L versus −15.5 mmol/L) compared to those who survived the initial 7 days. Conclusion: Initial Serum lactic acid and BD were found to be good prognostic indicators of early mortality in major thermal burns.